From Curative Habits to Preventive Care: Health Education and Shifting Dental Health Values in Makassar, Indonesia - Zulkarnain; Syamsu A Kamaruddin; Arlin Adam (Journal of Indonesian Scholars for Social Research, 2026)
This study examines how health education influences dental care behavior and contributes to shifting health values among urban communities in Makassar, Indonesia. Although dental and oral health is an essential component of overall well-being, preventive dental care is often treated as secondary to curative treatment, especially when individuals seek dental services only after experiencing pain or oral health problems. Using a sociological health perspective, this article explores how health education programs shape knowledge, attitudes, and everyday practices related to dental maintenance. The study highlights that health education delivered through campaigns, seminars, counseling, and educational materials can improve public awareness of oral hygiene, encourage regular tooth brushing, reduce harmful dietary habits, and promote routine dental check-ups. More importantly, the findings indicate a gradual shift in health values: dental care is increasingly understood not merely as a medical response to illness but as part of a preventive and healthy lifestyle. However, this behavioral transformation remains uneven. Socioeconomic barriers, particularly the cost of dental services and unequal access to adequate care, continue to limit the ability of low-income groups to translate knowledge into consistent practice. The study argues that effective dental health education must be integrated with broader efforts to reduce access inequalities. By linking behavioral change with social and economic contexts, this article contributes to sociological discussions on preventive health behavior, public health education, and value transformation in urban Indonesia.